2011
DOI: 10.3109/0886022x.2011.565140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease in Hypertensive Patients in Ghana

Abstract: Chronic kidney disease (CKD) is common in tropical Africa although there are few data on the prevalence of this disorder. Therefore we initiated a multicenter screening study to identify the prevalence and staging of CKD in 712 patients with known hypertension in four polyclinics in Accra, Ghana. We measured estimated glomerular filtration rate by the six-variable modification of diet in renal disease equation and proteinuria by the protein/creatinine ratio. All the subjects studied were Ghanaian. Of the 712 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
61
5
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 26 publications
13
61
5
3
Order By: Relevance
“…Risk markers associated with presence of albuminuria in Caucasians and Asians with hypertension include age, diabetes mellitus (DM), obesity, smoking, and insufficient blood pressure (BP) control . Knowledge on risk markers suggesting presence of albuminuria among patients with hypertension in sub‐Saharan Africa (SSA) has only been investigated in urban areas and is, in general, comparable with those of the Western world . The lifestyle and living conditions in rural areas of SSA differ from urban environments in terms of physical activity, nutrition, and patterns of cardiovascular disease .…”
mentioning
confidence: 99%
“…Risk markers associated with presence of albuminuria in Caucasians and Asians with hypertension include age, diabetes mellitus (DM), obesity, smoking, and insufficient blood pressure (BP) control . Knowledge on risk markers suggesting presence of albuminuria among patients with hypertension in sub‐Saharan Africa (SSA) has only been investigated in urban areas and is, in general, comparable with those of the Western world . The lifestyle and living conditions in rural areas of SSA differ from urban environments in terms of physical activity, nutrition, and patterns of cardiovascular disease .…”
mentioning
confidence: 99%
“…However, among hypertensive adults in four polyclinics in Accra, Ghana, Osafo et al [1] found a chronic kidney disease (CKD) prevalence of 46.9%. …”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a common complication of hypertensive patients in Ghana, with a prevalence ranging between 22%-46.9% among the general population [7,8]. Kidney disease and preeclampsia however, are caused by similar factors; both disorders have been linked to hypertension, obesity, insulin resistance and endothelial dysfunction [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%